Aspectos da Eletrodinâmica Quântica em dimensões espaciais extras - Girardi, Thalis José (2015)
In the present work are investigated some aspects of Quantum Electrodynamics, formulated in space-time dimension D = 4 + 1, 1-loop level approach. Among the aspects considered is the renormalization of the propagators and vertex. The calculation of the physical amplitudes is done so that all the arbitrariness inherent in this type of problem involved are preserved. The internal momenta are assumed arbitrary in order to preserve the possibility of dependence involved in such choice. An arbitrary scale is introduced in the separation of terms with different degrees of divergence in order to preserve the possibility of scaling ambiguities. The effects of regulation are avoided in the intermediate steps with the use of an appropriate strategy to deal the problem of divergences in perturbative solutions of Quantum Field Theories. With this attitude we got clear and wide conclusions about the consistency conditions involved in perturbative calculations in space-time dimension D = 4 + 1. The simplicity, combined with the general feature of the method, allows to believe that it can be used as an alternative to traditional methods of regulation, particularly in scenarios where such tools have restrictions of applicability or produce inconsistent results. The method can be applied in perturbation calculations related to theories expressed in extra space-time dimensions, with respect to the physical dimension D = 3 + 1, producing consistent results in even and odd dimensions.